Contribution and Distribution of Farmers Income of Palm Oil (Elaeis guineensis Jacq.) in Pewisoa Jaya Village Tanggetada Sub-District Kolaka Regency - Muhtar Amin; S. Sudirman (Universitas Sembilanbelas November Kolaka, 2019)
The objective to be achieved is to determine the contribution of oil palm farmers' income to the total income of farmers in Pewisoa Jaya Village, Tanggetada District, Kolaka Regency. To determine the income distribution of oil palm farmers in Pewisoa Jaya Village, Tanggetada District, Kolaka Regency. on the results of the study it can be concluded that the contribution and distribution of income of oil palm farmers is 25,10 % harvest season, the average income of oil palm farmers is 61,42 % per harvest year while the contribution of oil palm farming is 25.10% of the total income of oil palm farmers, and the distribution of income of oil palm farmers is 0.004. the condition is still very low or the community is less prosperous in Pewisoa Jaya Village, Tanggetada District, Kolaka Regency